2022
DOI: 10.3389/fpls.2022.956298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of salt tolerant wheat genotypes by using morpho-physiological, biochemical, and molecular analysis

Abstract: Food security is facing a major threat from salinity and there is a need to develop salt tolerant crop varieties to ensure that the demand for food from the world’s increasing population is met. Salinity mostly occurs in arid and semi-arid regions. It may cause many adverse physiological effects on plants, i.e., toxic ion accumulation, disturbed osmotic potential, and decreased crop yield. The present study aimed to investigate the morphological, physiological, biochemical, and genetic parameters of wheat geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The cultivar Akbar-2019 was heat tolerant, and it displayed better antioxidant activities, osmolyte accumulation, and nutrient uptake (Ca, Mg, and K), which resulted in better yields and yield traits in this cultivar. Our results are same as the findings of different authors, who also found that salt-tolerant cultivars displayed a better performance when compared to salt-sensitive cultivars [62,63].…”
Section: Discussionsupporting
confidence: 92%
“…The cultivar Akbar-2019 was heat tolerant, and it displayed better antioxidant activities, osmolyte accumulation, and nutrient uptake (Ca, Mg, and K), which resulted in better yields and yield traits in this cultivar. Our results are same as the findings of different authors, who also found that salt-tolerant cultivars displayed a better performance when compared to salt-sensitive cultivars [62,63].…”
Section: Discussionsupporting
confidence: 92%
“…Amino acids are precursors or donors for many fundamental compounds and are also major organic N forms for N allocation and reuse. The storage of amino acids promotes rapid plant recovery from adversity (Irshad et al, 2022; Tavernier et al, 2007), but there is also energy consumption for turnover and N resource costs. Enhancing the source‐to‐sink transport of free amino acids in leaves accelerates N utilization and seed yield (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is particularly useful in cases where candidate genes are unavailable. Among these markers, SSR markers serve as a potential tool for assessing the degree of genetic variation in salt tolerance in several crops [15,[31][32][33]46]. This approach offers numerous advantages that have already been mentioned in the Introduction section.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they provide objective data that can be analyzed. Among the various molecular markers available for genetic characterization, simple sequence repeat (SSR) or microsatellite markers are extensively used for cultivar identification, germplasm characterization, genetic diversity, and molecular mapping due to their numerous advantages, including cost-effectiveness, the presence of multi-alleles, high levels of polymorphism, high-throughput capabilities, abundance, co-dominant, locus-specificity, informative, lack of bias, and repeatability [15,[31][32][33]. Therefore, SSR markers can play a vital role with phenotypic traits in evaluating the salt tolerance of wheat genotypes and identifying the most salt-tolerant ones.…”
Section: Introductionmentioning
confidence: 99%